High-intensity running in English FA Premier League soccer matches - Bradley, P. S.; Sheldon, W.; Wooster, B.; Olsen, P.; Boanas, P.; Krustrup, P. (Journal of Sports Sciences, 2009)
The aims of this study were to (1) determine the activity profiles of a large sample of English FA Premier League soccer players and (2) examine high-intensity running during elite-standard soccer matches for players in various playing positions. Twenty-eight English FA Premier League games were analysed during the 2005-2006 competitive season (n = 370), using a multi-camera computerised tracking system. During a typical match, wide midfielders (3138 m, s = 565) covered a greater distance in high-intensity running than central midfielders (2825 m, s = 473, P = 0.04), full-backs (2605 m, s = 387, P < 0.01), attackers (2341 m, s = 575, P < 0.01), and central defenders (1834 m, s = 256, P < 0.01). In the last 15 min of a game, high-intensity running distance was ~20% less than in the first 15-min period for wide midfielders (467 m, s = 104 vs. 589 m, s = 134, P < 0.01), central midfielders (429 m, s = 106 vs. 534 m, s = 99, P < 0.01), full-backs (389 m, s = 95 vs. 481 m, s = 114, P < 0.01), attackers (348 m, s = 105 vs. 438 m, s = 129, P < 0.01), and central defenders (276 m, s = 93 vs. 344 m, s = 80, P < 0.01). There was a similar distance deficit for high-intensity running with (148 m, s = 78 vs. 193 m, s = 96, P < 0.01) and without ball possession (229 m, s = 85 vs. 278 m, s = 97, P < 0.01) between the last 15-min and first 15-min period of the game. Mean recovery time between very high-intensity running bouts was 72 s (s = 28), with a 28% longer recovery time during the last 15 min than the first 15 min of the game (83 s, s = 26 vs. 65 s, s = 20, P < 0.01). The decline in high-intensity running immediately after the most intense 5-min period was more evident in attackers (216 m, s = 50 vs. 113 m, s = 47, P < 0.01) and central defenders (182 m, s = 26 vs. 96 m, s = 39, P < 0.01). The results suggest that high-intensity running with and without ball possession is reduced during various phases of elite-standard soccer matches and the activity profiles and fatigue patterns vary among playing positions. The current findings provide valuable information about the high-intensity running patterns of a large sample of elite-standard soccer players, which could be useful in the development and prescription of specific training regimes.